Problems of genre classifications of Tuvan music folklore (illustrated by a song tradition) - Mongush, Ayasmaa D.-B. (The New Research of Tuva, 2009)
The article is devoted to the actual problems of genre classification of Tuvan music folklore and the differentiation of genres at Tuvan folk songs. Basing of the achievement of Russian ethnomusicology researchers, author analyzes the main works of Tuvan scientists on Tuvan music folklore and offers her point of view on the basis of modern researches connected with music culture of indigenous peoples of the North and Siberia.